Alcohol consumption among of first year Rzeszow’s universities students - Binkowska-Bury, Monika; Więch, Paweł; Sałacińska, Izabela; Januszewicz, Paweł (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. The problem of gradual consumption of alcoholic beverages among young people is a predictor of risk behaviors related to health. Alcoholism, criminal, traumas, risks during pregnancy increases the risk of cancer, liver disease — a few from among the consequences of excessive alcohol consumption, having a substrate both in adolescence and early adulthood. Aim. Assessment of the level of alcohol consumption among first year students of Rzeszow’s universities. Material and methods: In the period from October to December 2009 nine hundred twenty four students of first year of full-time studies at the University of Rzeszow and Rzeszow University of Technology were examined. They were divided according to the study discipline: medical (38.2%), exact sciences (30.9%) and humanities (30.9%). Selection of the research sample was deliberately. The study was performed with usage of a diagnostic survey questionnaire. Results and conclusions. Most of the students (95.2%) at least once in their live consumed alcoholic beverage (96.8% exact sciences, 95.5% medical, 92.9% humanities). Persons that declared drinking of alcohol, drank it at least once a month (30.3%) or once a week (27.8%). Almost every third student drank 1–2 portions (31.2%) of alcohol at time. Weekly consumption among the students concernedat most 1–2 portions (40.6%), or 10 and more portions (14.9%). The main reason for drinking alcohol by every other student was a celebration of success (49.0%). Statistically significant correlation between the frequency of alcohol consumption and the discipline of study (p = 0.0001) was proved.